Microwave-assisted Synthesis of 2-Styrylquinoline-4-carboxylic Acids as Antitubercular Agents - C. Muscia, Gisela; E. Asis, Silvia; Y. Buldain, Graciela (Medicinal Chemistry, 2017)
Background: Many 2-substituted quinolines and especially 2-arylvinyl derivatives isolated from plants or prepared by synthesis have been designed from ethnopharmacological studies. Objective: In order to explore new aspects of the structure-antituberculosis activity relationship, a series of styrylquinoline derivatives was prepared. Method: A series of styrylquinoline derivatives was prepared from quinaldic acid and a variety of arylbenzaldehydes under eco-friendly conditions via Knoevenagel reaction and trifluoroacetic acid (TFA) as catalyst. Results: The products were obtained in short reaction times and good yields and were evaluated for growth inhibitory activity towards Mycobacterium tuberculosis H37Rv (Mtb) through the National Institute of Allergy and Infectious Diseases (NIAID, USA). Conclusion: Three compounds had activity under aerobic conditions.
Keywords: Mycobacterium tuberculosis